WOUND HEALING ACTIVITY OF A HERBAL HYDROGEL OF A COMBINATION OF ETHANOL EXTRACT OF GOTU KOLA LEAVES (CENTELLA ASIATICA. L) AND HONEY ON MALE WISTAR RATS - Remanti, Etis
Hydrogel is a topical preparation that is used by rubbing it on the skin. Commonly used hydrogel bases include kappa carrageenan and sodium hyaluronate, but the combination of the two is still rarely found. Hydrogel can be combined with natural ingredients with wound healing activity, including the ethanol extract of gotu kola leaves and honey. The ethanol extract of gotu kola leaves contains asiaticoside, which has a wound-healing effect. Honey has tissueregeneration activity. Research was conducted to determine the effect of the combination of kappa carrageenan base and sodium hyaluronic acid. The ratio of kappa carrageenan solution and sodium hyaluronate in each base formula used is formula A (20:40), formula B (30:30), and formula C (40:20). Evaluations carried out on the formula include viscosity, spreadability, pH, homogeneity, and organoleptic. The selected base formula will be optimized with different concentrations of gotu kola extract, namely H1 preparation (0.5% ethanol extract of gotu kola leaves) and H2 preparation (1% ethanol extract of gotu kola leaves), and antibacterial activity and wound healing tests will be carried out. The results of the hydrogel formulation with a combination of kappa carrageenan and sodium hyaluronate bases influence the characteristic parameters of the herbal hydrogel formula, namely viscosity, spreadability, and pH. The results of the viscosity evaluation of the three formulas were A>B>C. The spread capacity of the formula A<B<C. The results of measuring the pH of formulas A, B, and C were 4.82, 4.71, and 4.56. From these characteristic parameters, formula B was selected, which will then be tested for its antibacterial activity and wound healing activity. The diameter of the inhibitory power of H1 and H2 preparations on Staphylococcus aureus bacteria was 10.69 + 1.25 mm and 12.13 + 1.07 mm, while the inhibitory power of Pseudomonas aeruginosa bacteria had a diameter of 9.15 + 0.27 mm and 11.37 + 0.41mm. The percentage of wound healing using H1 and H2 preparations in excision wounds at 21 days was 91.10 + 0.52 and 92.44 + 0.86. Meanwhile, healing for burn wounds was 33.91 + 15.19 and 57.56 + 13.32. It can be concluded that H1 and H2 preparations can inhibit the bacteria Staphylococcus aureus and Pseudomonas aeruginosa. Administration of H1 and H2 preparations showed increased wound healing in both wound models.